2021
DOI: 10.1080/16089677.2021.1877445
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical risk factors for morphometric vertebral fractures in older subjects in KwaZulu-Natal

Abstract: There are limited data on vertebral fractures (VFs) in South Africa (SA). Therefore a study was undertaken to compare the demographic profile, clinical risk factors and bone mineral density (BMD) in subjects aged 60 years and over with and without morphometric VFs. Patients and methods: In a descriptive case-controlled study, demographic data, clinical risk factors (CRF) and BMD were collected. Morphometric VFs were identified using the semi-quantitative Genant method. Descriptive analysis was undertaken using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In a study of 197 study volunteers >60 years of age living in Durban, South Africa, 20.8% had morphometric vertebral fractures on thoraco‐lumbar radiographs. There was no statistical difference in fracture prevalence between Black and Indian subjects in that study 85 . In a cohort of 430 postmenopausal women living in Kinshasa, Democratic Republic of Congo, who complained of back pain, vertebral fractures were diagnosed in 11% of the thoraco‐lumbar vertebrae; the prevalence of fractures rose with age 86 .…”
Section: Outcomes Of Inadequate Calcium Intakementioning
confidence: 67%
See 1 more Smart Citation
“…In a study of 197 study volunteers >60 years of age living in Durban, South Africa, 20.8% had morphometric vertebral fractures on thoraco‐lumbar radiographs. There was no statistical difference in fracture prevalence between Black and Indian subjects in that study 85 . In a cohort of 430 postmenopausal women living in Kinshasa, Democratic Republic of Congo, who complained of back pain, vertebral fractures were diagnosed in 11% of the thoraco‐lumbar vertebrae; the prevalence of fractures rose with age 86 .…”
Section: Outcomes Of Inadequate Calcium Intakementioning
confidence: 67%
“…There was no statistical difference in fracture prevalence between Black and Indian subjects in that study. 85 In a cohort of 430 postmenopausal women living in Kinshasa, Democratic Republic of Congo, who complained of back pain, vertebral fractures were diagnosed in 11% of the thoraco-lumbar vertebrae; the prevalence of fractures rose with age. 86 In the Gambia, a cross-sectional study of 488 healthy men and women >40 years of age from Kiang West were found to have a prevalence of 9% moderate or severe vertebral fractures on DXA.…”
Section: Regional Considerations High-income Countriesmentioning
confidence: 99%